Situating the Core and Structure of Experience in Constitutional Interpretation: Judicial Reasoning under the Indian Constitution - DAM, Shubhankar (Institutional Knowledge at Singapore Management University, 2007)
This article is about texts: texts of legal provisions and texts of judgments. How much does the text of a legal provision tell us about its meaning? How much does a judgment tell us about the reasons for any given meaning of the text? Rather than in the abstract, the article unfolds both these questions in the context of the Indian Constitution. More specifically, it unfolds the questions in the context of an issue of great constitutional importance the Indian Supreme Court was confronted with in B. R. Kapur v. State of Tamil Nadu and Another. Can a person convicted of a criminal offence be sworn in and contisnue to function as a Chief Minister of a State under the Indian Constitution? It was a constitutional issue and the Supreme Court came up with a constitutional answer: not surprisingly, it found reasons in the Constitution for doing so. How did the Court do so? What did the Court do to the texts to find the answers? What did the Court do in reproducing the answers in the text of its judgments? In trying to extricate the relation between the text reasons and its presentation in the judgment the article is divided into five sections. Section one prepares the ground work by introducing the facts and provisions relevant for our current purposes. Section two explores some of the past literature involving related facts and provisions while emphasizing on the conceptual distinctions that were ultimately critical for the Supreme Court in the instant case. Section three is a critique of the method of B. R. Kapur and the rationales employed to explain the relation between the texts of the provisions and the conclusions supposedly flowing from it. Section four proposes a critical realist critique of the earlier section: in particular the inevitability of a core for interpreting texts and a possible structure to conceptualize the experience of the core. Finally section five concludes with a call to move towards a poststructural account of judicial process so as to make better sense of that which goes by the name of constitutional interpretation and judicial activism in Indian public law.